Effect of repeated post-resistance exercise cold or hot water immersion on in-season inflammatory responses in academy rugby players: a randomised controlled cross-over design - Horgan, B. G.; West, N. P.; Tee, N.; Halson, S. L.; Drinkwater, E. J.; Chapman, D. W.; Haff, G. G. (European Journal of Applied Physiology, 2024)
Purpose Uncertainty exists if post-resistance exercise hydrotherapy attenuates chronic inflammatory and hormone responses. The effects of repeated post-resistance exercise water immersion on inflammatory and hormone responses in athletes were investigated.